2016
DOI: 10.3389/fpsyg.2016.01243
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Creativity as Predictor of Intrinsic Motivation and Academic Engagement in University Students: The Mediating Role of Positive Emotions

Abstract: Objective: Emotional creativity (EC) implies experiencing a complex emotional life, which is becoming increasingly necessary in societies that demand innovation and constant changes. This research studies the relation of EC as a dispositional trait with intrinsic motivation (IM) and academic engagement (AE).Methods: A sample of 428 university Chilean students, 36.5% men and 63.5% women, with ages from 18 to 45 years-old (M = 20.37; DT = 2.71). Additionally, the mediating function of class-related positive emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 78 publications
(111 reference statements)
3
58
0
10
Order By: Relevance
“…EI is key to overcoming the challenges that university students will face when they leave the classroom, during their careers, and in their personal and professional futures. Other research is in line with these results we have obtained in higher education (Oriol et al, 2016; Torrecilla-Sánchez et al, 2018). In fact, EI is key to overcoming the challenges that university students will face in these periods (Pavlin and Svetlik, 2012; Mok et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…EI is key to overcoming the challenges that university students will face when they leave the classroom, during their careers, and in their personal and professional futures. Other research is in line with these results we have obtained in higher education (Oriol et al, 2016; Torrecilla-Sánchez et al, 2018). In fact, EI is key to overcoming the challenges that university students will face in these periods (Pavlin and Svetlik, 2012; Mok et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In the same line, in investigations such as Oriol et al (2016), it is concluded that university students can understand the complexity of the emotional processes they undergo. A greater control of these emotions would allow students to maintain higher levels of interest in their studies at the different educational stages and to avoid the risk of school failure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is little sense in considering the act of learning as a rite of passage. Not only do a number of studies suggest the importance of emotion as a whole on learning (Maguire et al 2017;Oriol et al 2016), but others delve deeper and show that the type of emotion experienced by learners is important: autonomous motivation generates better learning than controlled motivation, whereby feelings of pride and guilt drive the desire to meet internalised social expectations (Cai & Liem 2017). In this model, failure can have real consequences, in which a hypercompetitive environment causes stress and mental illness (Posselt & Lipson 2016).…”
Section: Many Alternativesmentioning
confidence: 99%
“…Education is a key factor in explaining economic growth [3]. Students' performance is correlated with the national development of human capital accumulation, and any factor affecting the quality of human production will directly affect future economic growth.…”
Section: Problem Statementmentioning
confidence: 99%